PENGARUH PROFITABILITAS, LIKUIDITAS, DAN UKURAN PERUSAHAAN TERHADAP OPINI AUDIT GOING CONCERN - Enggar Nursasi; Firhan Syafrizal Davi; Abdul Kadir Usry (MEASUREMENT : Jurnal Program Studi Akuntansi, 2023)
The purpose of this study was to investigate the impact of Liquidity, Profitability, and Company Size on the Going Concern Audit assessment of automotive companies listed on the Indonesia Stock Exchange (IDX) for the period 2018 to 2021. The research uses a quantitative study that takes 56 automotive companies listed on the IDX as a population at the same time. Descriptive statistical analysis, logistic regression analysis, model feasibility test, coefficient of determination test, and hypothesis testing are all analytical methods used to process and assess the data collected in the study. The results showed that the Going Concern Audit Opinion of automotive companies on the IDX for the period 2018 to 2021 was influenced by liquidity, profitability, and company size factors